2022
DOI: 10.3390/nu14142898
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Biomarkers and Factors Correlated with Poor Sleep Status among Young Females: A Case-Control Study

Abstract: Poor sleep status is associated with several health problems. Nutritional biomarkers and factors related to poor sleep are understudied. This study aimed to identify nutrition biomarkers and factors related to sleep status in healthy young Saudi females. The study included 92 normal-weight and obese Saudi females aged 19–25. Fasting blood glucose, insulin, and lipid profiles were measured. Insulin resistance was calculated on the basis of the homeostasis model assessment of insulin resistance (HOMA-IR) method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…As our study showed the association of dialysis with hyperkalemia, it is essential to consider the patient's chronic illness and medications, which may influence potassium levels [ 28 ]. Additionally, it is important to take other potential confounding factors that affect sleep quality into consideration, such as stress, adiposity, and socioeconomic status into consideration [ 29 ]. Other hemodialysis centers with slightly different shift timings could also contribute to variations.…”
Section: Discussionmentioning
confidence: 99%
“…As our study showed the association of dialysis with hyperkalemia, it is essential to consider the patient's chronic illness and medications, which may influence potassium levels [ 28 ]. Additionally, it is important to take other potential confounding factors that affect sleep quality into consideration, such as stress, adiposity, and socioeconomic status into consideration [ 29 ]. Other hemodialysis centers with slightly different shift timings could also contribute to variations.…”
Section: Discussionmentioning
confidence: 99%
“…The numeric rating scale (NRS) is a common indicator to estimate the pain degree [27]. Pittsburgh sleep quality index (PSQI) is considered to be a crucial assessment system for sleep status [1]. The score of the short form 36 health survey questionnaire (SF-36) is used as a reflection of quality of life [3].…”
Section: Introductionmentioning
confidence: 99%
“…In our Special Issue entitled "Polyphenols and Polyphenol-Rich Foods in Neurodegenerative Disorders", several articles are published that provide further evidence on the potential role of polyphenols in brain health. The study of Al-Musharaf et al [21] investigated the association between dietary polyphenols and sleep quality in 92 normal-weight and obese young women, reporting that only higher polyphenol intake and homeostasis model assessment of insulin resistance (HOMA-IR) were inversely associated with poor sleep quality (with no significant findings for other nutritional-related biomarkers). Another two studies provided insights from animal models on Parkinson's and Alzheimer's diseases.…”
mentioning
confidence: 99%